Pengaruh Model Pembelajaran SQ3R Berbantu Wordwall Terhadap Hasil Belajar Siswa Pada Materi Sistem Indera - Azkiyatun Nisa; R. Ading Pramadi; Hadiansah Hadiansah (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
This research is motivated by problems that are often encountered in learning biology in the form of a lack of motivation to learn, which results in low student learning outcomes. The purpose of this study was to analyze the effect of the Wordwall-assisted Survey, Question, Read, Recite, Review (SQ3R) learning model on student learning outcomes on sensory systems. The method in this study was quasi-experimental with a non-equivalent control group design. The instruments used were observation sheets, multiple-choice questions and student response questionnaires. The results showed that the implementation of teacher and student activities was in a very good category. Student learning outcomes were analyzed using SPSS version 26 to obtain an Asymp value. Sig (2-tiled) is 0.018 < 0.05, thus the hypothesis is accepted, that is, there is an influence of the Wordwall-assisted SQ3R method on student learning outcomes. Student responses to the learning process of the SQ3R model assisted by Wordwall gave positive responses with very good interpretations. The conclusion of this study is that the Wordwall-assisted SQ3R learning model has a positive effect on student learning outcomes in sensory system material.